Customer knowledge and behavior on the use of food refrigerated display cabinets: A Portuguese case - Gonçalves, João Carlos (2022)
This article presents a study on customer knowledge and habits regarding the use of refrigerated display cabinets (RDC). The study was carried out on a sample of Portuguese retail stores’ customers, using a questionnaire survey available through an Internet platform. The sample consisted of 136 individuals, who voluntarily participated in the study. Questions included the characterization of the sociodemographic population involved. The questionnaire included different questions to related with RDC, namely customer knowledge about the appearance of each RDC equipment, questions to evaluate the respondents’ perception about the advantages and disadvantages related to open or glass-door closed RDC, questions to assess the participants’ habits and behavior when purchasing food products from glass-door closed RDC (frequency and duration of door open), questions to characterize the consumers’ habits on purchasing food products from RDC, and also questions to characterize the consumers’ shopping attitudes in the context of the COVID-19 pandemic, caused by SARSCoV- 2. The results seem to indicate that customers prefer closed RDC; for example, 61.8% of participants prefer products preserved in glass-door closed RDC, against 6.6% that admit to preferring products preserved in open RDC. Therefore, we can deduce that the existence of doors does not appear to be an obstacle to purchasing food products. Regarding the use of glass-door closed RDC, 80.1% of the participants say they just open the door once, and 53.7% of the costumers believe they keep the door open in the interval [4‒6 s]. This indicates that Portuguese customers are quite well informed about food safety issues and seem to follow assertive attitudeswhen purchasing food products from RDC. This study reinforces the benefits of replacing open RDC by closed glass-doors allowing significant energy savings.